Autologous Mesenchymal Stem Cell and Islet Cotransplantation: Safety and Efficacy. (21st November 2017) - Wang, Hongjun; Strange, Charlie; Nietert, Paul J.; Wang, Jingjing; Turnbull, Taylor L.; Cloud, Colleen; Owczarski, Stefanie; Shuford, Betsy; Duke, Tara; Gilkeson, Gary; Luttrell, Louis; Hermayer, Kathie; et al.
Abstract : Islet engraftment after transplantation is impaired by high rates of islet/β cell death caused by cellular stressors and poor graft vascularization. We studied whether cotransplantation of ex vivo expanded autologous bone marrow-derived mesenchymal stem cells (MSCs) with islets is safe and beneficial in chronic pancreatitis patients undergoing total pancreatectomy with islet autotransplantation. MSCs were harvested from the bone marrow of three islet autotransplantation patients and expanded at our current Good Manufacturing Practices (cGMP) facility. On the day of islet transplantation, an average dose of 20.0 ± 2.6 ×10 6 MSCs was infused with islets via the portal vein. Adverse events and glycemic control at baseline, 6, and 12 months after transplantation were compared with data from 101 historical control patients. No adverse events directly related to the MSC infusions were observed. MSC patients required lower amounts of insulin during the peritransplantation period ( p  = .02 vs. controls) and had lower 12-month fasting blood glucose levels ( p  = .02 vs. controls), smaller C-peptide declines over 6 months ( p  = .01 vs. controls), and better quality of life compared with controls. In conclusion, our pilot study demonstrates that autologous MSC and islet cotransplantation may be a safe and potential strategy to improve islet engraftment after transplantation. (Clinicaltrials.gov registration number: NCT02384018).